S and MPO – An information system for ozone spectroscopy on the WEB; Journal of Quantitative Spectroscopy and Radiative Transfer; Vol. 125 - Babikov Yu. L.; Mikhailenko S. N. Semen Nikolaevich; Barbe A.; Tyuterev Vl. G. (2014, 2014)
Title screen